2014
DOI: 10.1007/s11126-014-9312-8
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality in Non-Treatment Seeking Young Adults with Subsyndromal Gambling Disorder

Abstract: Gambling Disorder is associated with elevated rates of suicidal thoughts and acts. However, virtually nothing is known about suicidality in people with subsyndromal forms of gambling disorder. A total of 174 non-treatment seeking subjects were recruited for a study of impulsivity and met criteria for a subsyndromal form of DSM-5 gambling disorder (31.0 % females; mean age = 21.7 ± 3.61 years). Subjects were categorized as being 'at risk of suicide' or 'no suicide risk' based on the Mini-International Neuropsyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…(2014) used a subsyndromal GD sample and found an association between suicidality and anxiety disorders. However, the assessment of suicidality did not control for other mental disorders as this study did.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2014) used a subsyndromal GD sample and found an association between suicidality and anxiety disorders. However, the assessment of suicidality did not control for other mental disorders as this study did.…”
Section: Discussionmentioning
confidence: 99%
“…The annual cost of GD is approximately 5 billion US dollars within the United States alone (National Gambling Impact Study Commission & James, 1999). Subsyndromal gambling is also a notable concern, and is defined as a significant gambling activity that does not meet full DSM-5 criteria for GD (Grant, Derbyshire, Leppink, & Chamberlain, 2014). Subsyndromal gamblers also show high rates of depression, anxiety disorders, substance-use disorders, financial, legal, family, and professional problems (Cunningham-Williams et al., 1998; Desai, 2004; Gerstein et al., 1999; Grall-Bronnec et al., 2012; Potenza, Maciejewski, & Mazure, 2006; Shaffer & Korn, 2002; Welte, Barnes, Wieczorek, Tidwell, & Parker, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors' studies have revealed an increased suicidal behavior risk in people with affective and eating disorders. Thus, a high suicidal activity was found in people with mood disorders, anxiety (Grant, Derbyshire, Leppink, & Chamberlain, 2014), in people with neurotic symptoms (Cowlishaw & Kessler, 2016), as well as due to the use of psychoactive substances, addictive disorders (Bosc, Fatseas, Alexandre, & Auriacombe, 2012). https://doi.org/10.15405/epsbs.2020.01.83 Corresponding Author: K. V. Pyrkova Selection and peer-review under responsibility of the Organizing Committee of the conference eISSN: 770 As part of the third research direction, a number of works should be indicated on the family factor influence on the occurrence of suicidal readiness (Black et al, 2015;Jones et al, 2015).…”
Section: Problem Statementmentioning
confidence: 99%
“…1 PG may lead to both social and economic losses 1 and has been associated with poor general health 2 and elevated rates of suicidal thoughts and acts. 3 4 Furthermore, PG is associated with a higher prevalence of anxiety and depression compared with the normal population. 5 In Sweden, the estimated point prevalence of PG is approximately 2%, and the condition is classified as a public health problem.…”
Section: Introductionmentioning
confidence: 99%